Test on the Influence of Geometric Parameters of an Annular Trench on the Vibration Isolation Area - Jinglei Liu; Chuanqing Yu; Kai Li; Jie Liu; Mengyao Wen (Shock and Vibration)
To study the influence of annular trenches on a vibration isolation area, the depth, width, vibration source distance, and central angle of the trench are analysed as research variables, and a contour diagram of the amplitude reduction ratio is drawn based on an outdoor test of the trench. Taking an area with an amplitude reduction ratio less than 0.40 as the evaluation index of the effective vibration isolation area, the effects of the above geometric parameters on the vibration isolation area are analysed. Limited to the test conditions of this paper, the results show that the depth, vibration source distance, and deep width ratio are the important factors affecting the effective vibration isolation area; with the increase of the above parameters, the effective vibration isolation area increases significantly, but the area increase rate decreases gradually. The width has a relatively little effect on the effective vibration isolation area. When the ratio of depth to width is from 7.05 to 9.15, and the width reaches 0.23 times the Rayleigh wavelength, the annular trench can have a good effective vibration isolation area. When the central angle of the trench is less than 90°, a discontinuous effective vibration isolation area will form in the vibration isolation region. The selection of the central angle of the trench is related to the frequency. With the same trench size, the effective vibration isolation area decreases as frequency decreases. In addition, the effect of distance depth ratio on the effective vibration isolation area presents a fluctuation. When the ratio of distance to depth is from 1.21 to 2.05, a good effective vibration isolation area can be obtained and it is reasonable.